Foundations and social innovations - Steffen Bethmann (University of Basel, Center for Philanthropy Studies (CEPS), 2019)
Some voices argue that grant-making foundations are social innovators or the vanguard of society. Others see foundations as weak and encapsulated institutions, deprived of effective internal or external stimuli, and unable to deal with broad social problems. Both arguments have merit. While some foundations strive to change social routines, others support a theatre, a museum or a zoo. When do foundations decide to innovate? What determines their ability to do so? So far, there is little knowledge about the factors that influence foundation behavior and their capacity to innovate. Grant-making foundations have rarely received the attention of organizational theory. This paper addresses this theoretical lacuna by following an iterative research study approach of expert interviews and in-depth case studies. The results show that foundations are cultural capital and affection-driven as well as subject to strong inertial forces. Their organizational path is defined early in their existence. Their innovation capacity depends on their capital structure (social, cultural, financial, and symbolic) and their institutional imprints. The inferences found in the study allow for substantially advancing our understanding of foundations and their ability to innovate.
Keywords: 330; grant-making foundations; organizational theory; social innovation; case study